A flexible self-perceiving/repairing parachute (FSPRP) system adapted to the Martian dust storm environment. (August 2022) - Ding, Tianxiang; Hou, Xuyan; Zhu, Minglu; Zhou, Jie; Liu, Yuhui; Na, Zhonglai; Gao, Guowei; Zhang, Tao; Tan, Danielle S.; Wang, Yongbin; Chen, Tao; Yue, Honghao; et al.
Abstract: Rapid developments of deep space exploration technology are raising the requirements of more effective parachutes for achieving an efficient and reliable Entry-Descent-Landing (EDL) process of the Mars exploration mission. Martian dust storm as an extreme weather, usually causes significant challenges to Mars exploration missions. Alternatively, we propose a parachute system embedded with triboelectric dust-parachute collision sensors (TDPCS) and Shape Memory Alloy (SMA) based self-repairing mechanisms (SBSRM) as a cost-effective solution for EDL missions in the extreme Martian dust storm environment. The proposed triboelectric nanogenerator (TENG) based impact monitoring system is utilized for monitoring and estimating the damage position and damage degree of the parachute fabric. The SMA-based self-repairing system is utilized for reducing the stress concentration and strengthen local stiffness and strength around the damage hole. This parachute system shows a great potential of being an economic and advanced EDL module for supporting the extraterrestrial planet exploration missions. Graphical Abstract: ga1 Highlights: A parachute system with triboelectric dust collision sensors is proposed for Mars exploration mission. A Shape Memory Alloy (SMA) based self-repairing mechanism (SBSRM) is designed for parachute as a cost-effective solution. The proposed triboelectric sensor can monitor and estimate the damage position and degree of the parachute fabric. The SBSRM system can reduce the stress concentration and strengthen local stiffness around the damage hole.